2022
DOI: 10.1007/s00259-022-05931-5
|View full text |Cite
|
Sign up to set email alerts
|

The maximum standardized uptake value in patients with recurrent or persistent prostate cancer after radical prostatectomy and PSMA-PET-guided salvage radiotherapy—a multicenter retrospective analysis

Abstract: Purpose This study aims to evaluate the association of the maximum standardized uptake value (SUVmax) in positron-emission tomography targeting prostate-specific membrane antigen (PSMA-PET) prior to salvage radiotherapy (sRT) on biochemical recurrence free survival (BRFS) in a large multicenter cohort. Methods Patients who underwent 68 Ga-PSMA11-PET prior to sRT were enrolled in four high-volume centers in this retrospective multicenter study. Only patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This concept is corroborated by the specificity of the radioactive signal documented by the strict adherence of tracer uptake kinetics with the ligand-receptor model. Thus, in clinical studies assessing the prognostic value of PSMA PET imaging in early-stage PCa [ 10 13 , 15 , 47 ], the most common metrics adopted to quantify the PSMA-targeting tracer accumulation at PET imaging (i.e., SUV) may be influenced by several variables beyond FOLH1 expression, including PSMA-expressing cellular density or tumour burden. Based on our results, it can be hypothesized that the prognostic power of PSMA PET in this clinical setting might predominantly reflect these tumour characteristics rather than identifying a specific feature of PCa biological aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is corroborated by the specificity of the radioactive signal documented by the strict adherence of tracer uptake kinetics with the ligand-receptor model. Thus, in clinical studies assessing the prognostic value of PSMA PET imaging in early-stage PCa [ 10 13 , 15 , 47 ], the most common metrics adopted to quantify the PSMA-targeting tracer accumulation at PET imaging (i.e., SUV) may be influenced by several variables beyond FOLH1 expression, including PSMA-expressing cellular density or tumour burden. Based on our results, it can be hypothesized that the prognostic power of PSMA PET in this clinical setting might predominantly reflect these tumour characteristics rather than identifying a specific feature of PCa biological aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already reported a direct correlation between the degree of PSMA tracer uptake and histopathological features of disease severity, including the Gleason Score [ 9 12 ]. Coherently, the higher the PSMA tracer uptake by the primary tumour, the lower the long-term clinical outcome [ 13 ]. However, the PSMA PET prognostic penetrance is challenged by the acknowledged limitation of PET imaging that underestimates tracer concentration in small tumours and by the notion that 5–10% of clinically relevant PCa do not express this protein [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies with more patients and longer followup should assess this question. In addition, a study by Spohn et al proposed that the SUVmax value with the local recurrent disease on PSMA-PET/CT images might be a predictive factor for BRFS after sRT [15].…”
Section: Discussionmentioning
confidence: 99%
“…These cutoffs were not externally validated, and it is generally challenging to translate SUV-derived cutoffs in the clinical setting [ 39 ]. Nevertheless, former studies tentatively explored the discriminative potential of SUV-derived cutoffs in [ 68 Ga]Ga-PSMA-11 PET/CT, even in multicentric settings [ 40 ]. Moreover, ΔSUVmax minimizes the effects of many confounding factors representing the difference between late- and early-phase imaging in the same patient.…”
Section: Discussionmentioning
confidence: 99%